Liver Transplantation With Grafts From Super Obese Donors. Issue 10 (October 2021) - Vargas, Paola A.; Cullen, J. Michael; Argo, Curtis; Henry, Zachary; Stotts, Matthew J.; Intagliata, Nicolas; Northup, Patrick; Oberholzer, Jose; Pelletier, Shawn; Goldaracena, Nicolas
Abstract : Background: There are limited data on liver transplant (LT) outcomes with grafts from super obese donors. The present study aims to evaluate a unique cohort of recipients following LT using grafts from donors with body mass index (BMI) ≥50. Methods: Patients receiving grafts from donors with BMI ≥50 and BMI <50 from 2010 to 2019 were identified. A 1:2 case–control match was conducted to compare outcomes between the groups. Survival was analyzed using the Kaplan-Meier curves. Results: Six hundred sixty-five adult LTs were performed in the study period. Eighteen patients receiving a graft from a donor with BMI ≥50 were identified and matched to 36 patients receiving a graft from a donor with BMI <50. Grafts from male donors were significantly lower in the donor BMI ≥50 group when compared with the donor BMI <50 group (16.7% versus 66.7%, P = 0.001). Liver biopsy was performed in 77.8% of grafts in the donor BMI ≥50 group, whereas only in 38.8% of the grafts in the donor BMI <50 group ( P = 0.007). Recipients in the donor BMI ≥50 group had a significantly higher diagnosis rate of hepatocellular carcinoma pretransplant versus the donor BMI <50 group (38.9% versus 8.3%, respectively; P = 0.006). Major complications within 30 d did not differ statistically between groups. Biliary complications within the first 30 d were equal among groups (16.7%). Subanalysis comparing the super obese donor group versus the nonobese donor group showed no differences in terms of postoperative complications, readmission rate, graft rejection, or major complications including the need for reoperation, retransplantation, or mortality. Graft and patient survival at 1-, 3-, and 5-y graft were similar between the donor BMI ≥50 group versus donor BMI <50 group (94%/89%/89% versus 88%/88%/88%, P = 0.89, and 94%/94%/94% versus 88%/88%/88%, P = 0.48, respectively). Conclusions: LT with carefully selected grafts from super obese donors can be safely performed with outcomes comparable with non–super obese donor livers. Therefore, these types of grafts could represent a safe means to expand the donor pool. Abstract : Supplemental Digital Content is available in the text.